Do Shareholder Leverage Constraints Affect Debtholders? - Huang, Xiaoran; Massa, Massimo; Zhang, Lei (Journal of Financial and Quantitative Analysis, 2026)
We examine the relationship between shareholder leverage constraints and corporate risk-taking, focusing on its impact on debtholders. Our findings show that mutual fund leverage constraints are related to more risk-taking activities of portfolio companies, inducing higher credit risk and greater risk-shifting concerns for the firms’ debtholders. In response, the debtholders raise borrowing costs and tighten lending conditions. These effects intensify for firms facing higher levels of conflict between debtholders and shareholders and when mutual funds exert greater influence over firms. Econometric analyses, including instrumental variable specifications and asset management company mergers, support a causal interpretation.